2020
DOI: 10.13057/biodiv/d211009
|View full text |Cite
|
Sign up to set email alerts
|

The practice and plants used in Besale ritual healing by the Anak Dalam Tribe in Nyogan Village, Jambi, Indonesia

Abstract: Abstract. Asra R, Silalahi M, Fijridiyanto IA. 2020. The practice and plants used in Besale ritual healing by the Anak Dalam Tribe in Nyogan Village, Jambi, Indonesia. Biodiversitas 21: 4529-4536. The Anak Dalam Tribe (ADT) is an indigenous ethnic which inhabits the center of Sumatra, especially in Jambi and South Sumatra Provinces, Indonesia. The ADT communities still maintain their traditional rituals; one of them is the Besale ritual healing (BRH). This study aims to analyze the diversity of plants used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…According to data from the Research on Medicinal Plants and Traditional Herbal Medicine (Indonesian: Riset Tanaman Obat dan Jamu [RISTOJA]) in 2015, the Bukit Dua Belas Forest Area, located in Sarolangun Bangko Regency, Bungo Tebo Regency, and Batanghari Regency of Jambi Province, is home to 182 plant species used in herbal remedies for skin care. However, among these, only five plant species are specifically utilized by the SAD community for their skincare treatments [ 35 , 36 ]. The literature review reveals that only 30 plant species have been identified for their anti-aging properties.…”
Section: Herbs With Anti-aging Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to data from the Research on Medicinal Plants and Traditional Herbal Medicine (Indonesian: Riset Tanaman Obat dan Jamu [RISTOJA]) in 2015, the Bukit Dua Belas Forest Area, located in Sarolangun Bangko Regency, Bungo Tebo Regency, and Batanghari Regency of Jambi Province, is home to 182 plant species used in herbal remedies for skin care. However, among these, only five plant species are specifically utilized by the SAD community for their skincare treatments [ 35 , 36 ]. The literature review reveals that only 30 plant species have been identified for their anti-aging properties.…”
Section: Herbs With Anti-aging Propertiesmentioning
confidence: 99%
“…To apply it, the leaves are crushed and applied to the affected itchy skin. Furthermore, other parts of the tree, including the stem, bark, roots, and fruits, are commonly employed for the treatment of various ailments [ 36 , 82 ]. Many SAD people use surian stems as building material to make pillars for their houses, the bark is used as a diarrhea medicine and astringent, the roots are used as a detoxifier while the fruit is used to treat eye infections.…”
Section: Herbs With Anti-aging Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon shows that Indonesian netizens like a lot of trance shows. So, it's not surprising that many content creators suddenly become psychics and summon spirits by inserting them into A large number of viewers of trance shows on Youtube is inseparable from the collective belief system of people in Indonesia who believe in the world of ghaib and mystical (Asra et al, 2020;Handoko & Green, 2020;Herrmans, 2021). Shamans and the supernatural in the era before the internet and social media were secretive and could not be witnessed in person.…”
Section: Types Of Trance Content On Indonesian Youtube Channelmentioning
confidence: 99%
“…Exploration of medicinal plants' potential is still not optimal because they must compete with synthetic drugs. Therefore, it is paramount to conduct research on the use of traditional medicine by SAD in Nyogan village and its conservation efforts (Asra et al, 2020;Kurniawan & Syafri, 2020).…”
Section: Introductionmentioning
confidence: 99%